Pathology or source of power? The construction and experience of premenstrual syndrome within two contrasting cases. (August 2014) - Ussher, Jane M; Perz, Janette; May, Emily
This research examines the construction and experience of premenstrual syndrome (PMS) in the context of intimate couple relationships, through examination of two contrasting cases analysed using thematic decomposition of narrative interviews. Judith and her male partner pathologised premenstrual change, constructing the premenstrual self as out of control, and the epitome of the 'monstrous feminine'. Judith reported feeling over-burdened and uncontrollably angry premenstrually, associated with relationship issues and absence of partner recognition or support. In contrast, Sophia normalised premenstrual change, challenging the association between PMS and the construction of woman as deviant or dysfunctional. Sophia reported heightened energy and creativity premenstrually, and engaged in self-care supported by her woman partner. These cases demonstrate that premenstrual distress is an intersubjective experience, with constructions and material practices within relationships providing the context for premenstrual women being positioned as pathological and needing to be contained, or conversely, as sensitive and needing support.